Pengaruh Work-Family Conflict dan Motivasi Kerja Terhadap Komitmen Organisasi pada UPT Balai Monitor Spektrum Frekuensi Radio Kelas I Pekanbaru - Sephia Prihatin Sisi Wulandari; Ade Ria Nirmala (Al-Manar Journal of Economic and Social Studies, 2025)
UPT Balai Monitor Pekanbaru Class I Radio Frequency Spectrum is a technical implementing unit under the Directorate General of Resources and Equipment of Post and Information Technology (Ditjen SDPPI), responsible for monitoring and controlling radio frequencies in the Riau region. This study aims to analyze the influence of work-family conflict and work motivation on organizational commitment. The research employed a quantitative method with a survey approach, using questionnaires distributed to 35 out of 47 employees through purposive sampling. The data were analyzed using SPSS. The results indicate that work-family conflict does not have a significant partial effect on organizational commitment, while work motivation has a significant effect. Simultaneously, both independent variables influence organizational commitment. These findings underscore the importance of addressing employee motivation and considering the potential impact of work-family conflict on organizational commitment.